Anatomic Distribution of Colorectal Adenocarcinoma in Young Patients. Issue 8 (August 2019) - Lu, Pamela; Fields, Adam C.; Vise, Allison S.; Shabat, Galyna; Irani, Jennifer L.; Bleday, Ronald; Goldberg, Joel E.; Melnitchouk, Nelya
Abstract : BACKGROUND: The incidence of colorectal cancer has increased in the younger population. Studies show an increased prevalence of left-sided tumors in younger patients; however, exact anatomic distribution is not known. OBJECTIVE: We sought to determine the anatomic distribution of colorectal cancer in young patients and to calculate the proportion of tumors that would be within reach of a flexible sigmoidoscopy. DESIGN: The National Cancer Database (2004–2015) was used to identify patients with colorectal cancer. SETTINGS: This was a multicenter study using national data. PATIENTS: The study included 117, 686 patients under the age of 50 years diagnosed with colorectal cancer and 1, 331, 048 patients over the age of 50 years diagnosed with colorectal cancer. MAIN OUTCOME MEASURES: The primary outcome was the proportion of left-sided tumors in patients under the age of 50 years. RESULTS: A total of 74.4% of patients under age 50 years and 56.1% of patients over age 50 years had left-sided colorectal cancer. LIMITATIONS: The study is a retrospective review and does not exclude young patients who developed colorectal cancer with familial syndromes with a colorectal cancer disposition. CONCLUSIONS: A total of 74.4% of colorectal cancers diagnosed before age 50 years are left sided. In light of recent changes to screening recommendations, distribution of disease in young patients is important to both provider and patient education and decision-making. See Video Abstract at http://links.lww.com/DCR/A966 .